UNDERAGE MARRIAGE: ASSERTING 'BAPAK'S DOMINATION OVER GIRLS FROM TRADITIONAL SETTING TO PATRIARCHY - Jalaluddin B (Profetik: Jurnal Komunikasi, 2022)
According to the public, under-age marriage was a social matter that was contrary to social norms. However, it did not happen to the people of Kasisang's belief in Bantaeng Regency. The legacy of tradition, it was they thought about the under-age marriage which needed to be preserved. This study focused on the social-economic conditions and patriarchal culture behind the tradition. This study used the qualitative method with Simone de Beauvoir's existentialist phenomenological approach as the unit of data analysis by in-depth interview technique and analysis of document to gain crucial information. The technique analysis data by Colaizzi was used to analyze data founding. The results of this study proved that the tradition had long been a social-economic institution of the community there. Reducing promiscuity and economic affairs were the main motivation of this tradition. In addition, this tradition also legalized patriarchal culture which got Structured, Massive, and Systematic support (SMS) from social institutions, so that the culture was naturally well carried out. Considering all these things, the re-consistency and firmness of each regional institution needed to be performed with careful, coordinated, and full of commitment, so that it could confine the mobility of the tradition besides doing socialization and providing adequate employment opportunities for the community there in advance.